Removal of retained products of conception showing marked vascularity without uterine artery embolization: Two case reports. Issue 8 (28th June 2018) - Usui, Hirokazu; Sato, Asuka; Okayama, Jun; Suzuki, Yoshiya; Omoto, Akiko; Shozu, Makio
Abstract: Retained products of conception with marked vascularity can cause massive postabortal or post‐partum bleeding. Uterine artery embolization is effective for uterus preservation but does not assure fertility preservation. Thus, the optimal treatment for retained products of conception with marked vascularity is uncertain. Here, we report two cases of retained products of conception with marked vascularity: one early abortion and one hydatidiform mole, which were successfully resolved by dilation and removal of the retained products, without uterine artery embolization. We pretreated the cervical dilation using two or more laminaria tents and named this technique the 'maximum laminaria procedure'. We observed that the vascularity disappeared just after the laminaria tents were removed, and subsequently, we could remove the retained products with minimal bleeding, without uterine artery embolization. This protocol might become a standard treatment for retained products of conception with marked vascularity.